Public Perception of The Free Nutritious Meal Program in Tahalak Village Ujunggading - Resty Etika Pulungan; Efi Brata Madya (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to analyze community perceptions of the implementation of the Free Nutritious Meal Program (MBG) in Tahalak Ujung Gading Village, Batang Angkola District, South Tapanuli Regency. The MBG program is a government policy aimed at improving the nutritional status of the community, especially school children, and supporting the quality of human resources. This study uses a qualitative approach with a phenomenological design to understand the community's experiences and views on the program. Research informants were selected through a purposive sampling technique, including parents of students, teachers, village officials, and community leaders. Data collection was carried out through in-depth interviews, observation, and documentation, then analyzed through data reduction, theme categorization, and meaning drawing. The results of the study indicate that in general the community has a positive perception of the MBG program. For parents, this program is seen as economic assistance that can reduce household expenses, while for teachers, this program helps improve students' concentration and focus on learning. Village officials and community leaders view this program as a form of government concern for community welfare. However, the study also found several technical obstacles such as delays in food distribution, limited menu variety, and lack of information to parents regarding the program's implementation. Overall, the MBG program is considered to provide tangible benefits to the community and has the potential to improve family welfare and the quality of learning in schools. Therefore, improvements in coordination, communication, and menu variety are needed to ensure optimal and sustainable program implementation.